How does performance-based financing affect the availability of essential medicines in Cameroon?: A qualitative study - Sieleunou, Isidore; De Allegri, Manuela (Health policy and planning, 2019)
Performance-based financing (PBF) is being implemented across low- and middle-income countries to improve the availability and quality of health services, including medicines. Although a few studies have examined the effects of PBF on the availability of essential medicines (EMs) in low- and middle-income countries, there is limited knowledge of the mechanisms underlying these effects. Our research aimed to explore how PBF in Cameroon influenced the availability of EMs, and to understand the pathways leading to the experiential dimension related with the observed changes. The design was an exploratory qualitative study. Data were collected through in-depth interviews, using semi-structured questionnaires. Key informants were selected using purposive sampling. The respondents (n = 55) included health services managers, healthcare providers, health authorities, regional drugs store managers and community members. All interviews were recorded, transcribed and analysed using qualitative data analysis software. Thematic analysis was performed. Our findings suggest that the PBF programme improved the perceived availability of EMs in three regions in Cameroon. The change in availability of EMs experienced by stakeholders resulted from several pathways, including the greater autonomy of facilities, the enforced regulation from the district medical team, the greater accountability of the pharmacy attendant and supply system liberalization. However, a sequence of challenges, including delays in PBF payments, limited autonomy, lack of leadership and contextual factors such as remoteness or difficulty in access, was perceived to hinder the capacity to yield optimal changes, resulting in heterogeneity in performance between health facilities. The participants raised concerns regarding the quality control of drugs, the inequalities between facilities and the fragmentation of the drug management system. The study highlights that some specific dimensions of PBF, such as pharmacy autonomy and the liberalization of drugs supply systems, need to be supported by equity interventions, reinforced regulation and measures to ensure the quality of drugs at all levels.